Bacterial diversity in aquatic and other environments: what 16S rDNA libraries can tell us - Kemp, Paul F; Aller, Josephine Y (FEMS microbiology ecology, 2004)
We evaluate the substantial amount of information accumulated on bacterial diversity in a variety of environments and address several fundamental questions, focusing on aquatic systems but including other environments to provide a broader context. Bacterial diversity data were extracted from 225 16S rDNA libraries described in published reports, representing a variety of aquatic and non-aquatic environments. Libraries were predominantly composed of rare phylotypes that appeared only once or twice in the library, and the number of phylotypes observed was correlated with library size (implying that few libraries are exhaustive samples of diversity in the source community). Coverage, the estimated proportion of phylotypes in the environment represented in the library, ranged widely but on average was remarkably high and not correlated with library size. Phylotype richness was calculated by methods based on the frequency of occurrence of different phylotypes in 194 libraries that provided appropriate data. For 90% of aquatic-system libraries, and for 79% of non-aquatic libraries, the estimated phylotype richness was <200 phylotypes. Nearly all of the larger estimates were in aquatic sediments, digestive systems and soils. However, the approaches used to estimate phylotype richness may yield underestimates when libraries are too small. A procedure is described to provide an objective means of determining when a library is large enough to provide a stable and unbiased estimate of phylotype richness. A total of 56 libraries, including 44 from aquatic systems, were considered ‘large enough’ to yield stable estimates suitable for comparing richness among environments. Few significant differences in phylotype richness were observed among aquatic environments. For one of two richness estimators, the average phylotype richness was significantly lower in hyperthermal environments than in sediment and bacterioplankton, but no other significant differences among aquatic environments were observed. In general, and with demonstrated exceptions, published studies have captured a large fraction of bacterial diversity in aquatic systems. In most cases, the estimated bacterial diversity is lower than we would have expected, although many estimates should be considered minimum values. We suggest that on local scales, aquatic bacterial diversity is much less than any predictions of their global diversity, and remains a tractable subject for study. The global-scale diversity of aquatic Bacteria, on the other hand, may be beyond present capabilities for effective study.